Treatment Strategy for Aneurysms of the Posterior Cerebral Artery - Suzuki, O. (Centauro S.r.l., 2003)
The authors carried out a retrospective review of the records of 12 patients with aneurysms of the posterior cerebral artery (PCA). Four were asymptomatic, 1 presented with a mass effect, and 7 with a subarachnoid haemorrhage (SAH). Of the 7 ruptured aneurysms, 3 were embolized and 2 were clipped. However, 2 patients died from rebleeding before any treatment. Of the 5 unruptured aneurysms, 1 was embolized with coils but the remaining 4 have been conservatively observed. No aneurysms have ruptured during the follow-up period, and 3 have thrombosed spontaneously. According to our results, the PCA aneurysms should be treated aggressively in the early phase. Although the preservation of the anatomical integrity of the PCA should naturally be one of the prime objectives, PCA occlusion may sometimes be inevitable when treating large or fusiform aneurysms. On the other hand, conservative therapy is one of the options for the treatment of incidentally encountered unruptured ones, because these have the possibility of spontaneous thrombosis.